2023
DOI: 10.1002/mp.16356
|View full text |Cite
|
Sign up to set email alerts
|

Rapid estimation of patient‐specific organ doses using a deep learning network

Abstract: BackgroundPatient‐specific organ‐dose estimation in diagnostic CT examinations can provide useful insights on individualized secondary cancer risks, protocol optimization, and patient management. Current dose estimation techniques mainly rely on time‐consuming Monte Carlo methods or/and generalized anthropomorphic phantoms.PurposeWe proposed a proof‐of‐concept rapid workflow based on deep learning networks to estimate organ doses for individuals following thorax Computed Tomography (CT) examinations.MethodsCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…While Gerard et al [ 5 ] proposed Reg3DNet+ residual regression convolutional neural network to directly regress high-resolution images of local tissue volume changes from CT images.Through image registration between total vital capacity and lung volume under functional residual capacity, using tissue mass and structure-preserving registration algorithms, it was possible to obtain a direct estimation of regional lung volume changes from both paired and single CT images.Furthermore, Marios [ 6 ] developed a fast proof-of-concept workflow based on deep learning networks for assessing individual organ doses after chest computed tomography(CT) examinations.The study leveraged an independent dataset consisting of 19 patients for each network for organ dose prediction.Huo et al [ 7 ] employed several machine learning algorithms to construct a classification and prediction model for early aortic dissection patients,to facilitate the identification of potential dissection cases among misdiagnosed patients.Among the models built,the Bayesian network achieved an 84.55% accuracy, with an Area Under Curve(AUC) of 85.7%.Singh et al [ 8 ],on the other hand, developed a deep learning model to automatically assess aortic dissection in chest CT images.They trained the model with 4235 images from 30 patients (15 dissection cases and 15 non-dissection cases) and tested it on 3423 images obtained from 40 patients (20 dissection cases and 20 non-dissection cases),using a pretrained inception-v3 [ 9 ] network as the classification model.The study demonstrated the efficacy of deep convolutional neural networks in the recognition of aortic dissection, achieving an AUC of 97% and a sensitivity of 100%.In their research, Lee et al [ 10 ] utilized a generative-discriminative learning approach to predict object boundaries in medical image datasets, applying it to true and false lumen segmentation in aortic dissection. Kovács et al [ 11 ] employed De-scoteaux's method to measure the intimal flap in the segmented CT image after segmenting the aortic image.…”
Section: Introductionmentioning
confidence: 99%
“…While Gerard et al [ 5 ] proposed Reg3DNet+ residual regression convolutional neural network to directly regress high-resolution images of local tissue volume changes from CT images.Through image registration between total vital capacity and lung volume under functional residual capacity, using tissue mass and structure-preserving registration algorithms, it was possible to obtain a direct estimation of regional lung volume changes from both paired and single CT images.Furthermore, Marios [ 6 ] developed a fast proof-of-concept workflow based on deep learning networks for assessing individual organ doses after chest computed tomography(CT) examinations.The study leveraged an independent dataset consisting of 19 patients for each network for organ dose prediction.Huo et al [ 7 ] employed several machine learning algorithms to construct a classification and prediction model for early aortic dissection patients,to facilitate the identification of potential dissection cases among misdiagnosed patients.Among the models built,the Bayesian network achieved an 84.55% accuracy, with an Area Under Curve(AUC) of 85.7%.Singh et al [ 8 ],on the other hand, developed a deep learning model to automatically assess aortic dissection in chest CT images.They trained the model with 4235 images from 30 patients (15 dissection cases and 15 non-dissection cases) and tested it on 3423 images obtained from 40 patients (20 dissection cases and 20 non-dissection cases),using a pretrained inception-v3 [ 9 ] network as the classification model.The study demonstrated the efficacy of deep convolutional neural networks in the recognition of aortic dissection, achieving an AUC of 97% and a sensitivity of 100%.In their research, Lee et al [ 10 ] utilized a generative-discriminative learning approach to predict object boundaries in medical image datasets, applying it to true and false lumen segmentation in aortic dissection. Kovács et al [ 11 ] employed De-scoteaux's method to measure the intimal flap in the segmented CT image after segmenting the aortic image.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the management of patients treated with selective internal radiation therapy (SIRT) for the treatment of liver malignancies requires CE-CT for the delineation of the tumoral tissues, perfused liver lobe and organs at risk towards personalized dosimetry. 3 Artificial intelligence (AI) and particularly deep learning has shown very promising performance in multiple tasks, including image segmentation, [4][5][6] image generation, 7,8 dosimetry, [9][10][11] and classification. 12,13 However, the number of clean and reliable data available is still the bottle neck for generalizability and robustness of deep learning models.…”
Section: Introductionmentioning
confidence: 99%